2014
DOI: 10.4103/0973-8258.126814
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic toxicity study of Brahmi ghrita in rodents

Abstract: Context: Brahmi Ghrita (BG) contains Brahmi (Bacopa monneri), Vacha (Acorus calamus), Kushtha (Saussurea lappa), Shankhapushpi (Convolvulus pluricaulis) and Puran Ghrita, mentioned for treatment of various diseases. Aim: To assess acute and sub-chronic toxicity of Brahmi Ghrita in mice and rats, respectively. Materials and Methods: In acute toxicity study, Swiss strain albino mice were administered orally Brahmi Ghrita doses of 1, 2.5 and 5 g/kg and observed for behavioural changes and mortality, if any. In su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…[374] Furthermore, various researchers conducted toxicity studies on various Bacopa monnieri formulations, such as Deo et al, compiled acute and subchronic toxicity studies of Brahmi ghrita in rodents and concluded that Brahmi ghrita is safe in rodents and mice at doses of 1, 2.5, and 5 g/kg, p.o. [375] Similarly, no evidence of toxicity was found in a 90-day subchronic oral toxicity study in rats of BacoMind, an enriched phytochemical composition derived from Bacopa monnieri, at doses of 85, 210, and 500 mg/kg, in terms of clinical effects, neurological examination, weight gain, or hematological parameters. There were no signs of degradation after a necropsy and histopathological examination.…”
Section: Bacopa Monnieri Toxicity Spectrum and Herb-drug Interactionsmentioning
confidence: 99%
“…[374] Furthermore, various researchers conducted toxicity studies on various Bacopa monnieri formulations, such as Deo et al, compiled acute and subchronic toxicity studies of Brahmi ghrita in rodents and concluded that Brahmi ghrita is safe in rodents and mice at doses of 1, 2.5, and 5 g/kg, p.o. [375] Similarly, no evidence of toxicity was found in a 90-day subchronic oral toxicity study in rats of BacoMind, an enriched phytochemical composition derived from Bacopa monnieri, at doses of 85, 210, and 500 mg/kg, in terms of clinical effects, neurological examination, weight gain, or hematological parameters. There were no signs of degradation after a necropsy and histopathological examination.…”
Section: Bacopa Monnieri Toxicity Spectrum and Herb-drug Interactionsmentioning
confidence: 99%